Study on Direct Writing of Gallium Metal for the Flexible Sensor - Junfeng Liu; Haopeng Ma; Yong Yang; Weimin Yang; Zhiwei Jiao; Yuan Yu (Advances in Materials Science and Engineering)
There is an urgent need for a simple and effective method to manufacture flexible sensors composed of liquid metal. Gallium (Ga) metal has become an ideal flexible conductive material due to its high conductivity, low melting point, and high flow characteristics. In this paper, liquid Ga metal is directly written on the polyvinyl alcohol (PVA) film through the driving mode of piston extrusion; then, the Ga metal wire is transferred and sealed with silica gel. The advantages of piston mode are studied, and the direct writing parameters of the liquid Ga metal, including extrusion speed, nozzle height, printing speed, and nozzle inner diameter, are systematically optimized. The flexible sensor based on the sealed liquid Ga metal has good resilience under the external load. This work provides a specific reference for direct writing of liquid Ga metal and its sealing technology for the flexible sensor.